THE USE OF ARCHAIC WORDS IN THE NOVEL "AGABIY" BY K. KARIMOV (American Journal of Pedagogical and Educational Research, 2023)
This article deals with archaic words in the novel "Agabiy" by the Karakalpak writer K. Karimov.